Foreign-body reaction to an alveolar dressing (Alvogyl®): Presentation of 4 cases - Sotorra-Figuerola, Didac; Alberdi-Navarro, Javier; Gainza-Cirauqui, Maria-Luisa; Muñoz-Zapata, Juan Pablo; Aguirre-Urizar, Jose-Manuel (Journal of Oral Diagnosis, 2019)
Introduction: Alvogyl® is a product used for prevention and management of alveolar osteitis/dry-socket. Its active ingredients, iodoform (antiseptic) and butamben (anaesthetic), are transported in Penghawar djambivegetable fibresthat possess a hemostatic property. Patients: We present 4 clinical cases of a foreign-body reaction after retaining Alvogyl® in the extraction socket in two men and one woman, with a mean age of 52 years (37-66 years). Of these, two cases were in the maxilla and two in the mandible. All cases presented with a chronic inflammatory foreign-body reaction containing giant multinucleated cells and a fibrillar material. Conclusion: Alvogyl® is a product for the management of alveolar osteitis/dry-socket that should be removed from the alveolus once the pain has resolved for an adequate healing process to occur.